PERBEDAAN AKTIVITAS FISIK PADA ANAK OBESITAS DAN TIDAK OBESITAS DI SEKOLAH AL-ISLAH KOTA GORONTALO - Fitri Yani Arbie; Rahma Labatjo; Novian Swasono Hadi (JOURNAL HEALTH AND NUTRITIONS, 2018)
ABSTRACT Background: Obesity at children may impact health negatively for instance coronary heart disease and hypertension. Number of obesity suffering at children keeps increasing as change of eating pattern and life style. Less physical activity can influence weight. Data of Riskesdas in 2010 shows that prevalence of obesity at babies in Gorontalo Province is 7,8%. Objective: it aims to investigate risk factor of physical activity on obesity at children of TK Al-Islah of Gorontalo City in 2017. Research Methodology: research design applies case control. Research samples are 50 children of pre-school. The research samples are divided into 25 children with normal nutritional status and 25 children with obesity nutritional status. Nutritional status is determined by calculation of z-score of IMT/U. Variable of physical activity is determined based on calculation of questionnaire result that is adapted from Baecke’s research. The research is conducted in TK Al-Islah, Kota Tengah, Gorontalo City. It is conducted from July to August 2017. Research finding: Physical activity at students of TK Al-Ishlah, Gorontalo City, physical activity category is good for 56,0%, less good physical activity is 44,0%. Good physical activity and not obesity is 80,0% while good physical activity and obesity is 32,0%. Less good physical activity and not obesity is 20,0% while less good physical activity and obesity is 68,0%. There is correlation of physical activity with students’ nutritional status (IMT/U) at TK Al-Islah in 2017. Keywords: physical activity, obesity, school-aged children ABSTRAK Latar Belakang: Obesitas pada anak dapat berdampak negative bagi kesehatan. Contohnya penyakit jantung koroner dan hipertensi. Jumlah penderita obesitas pada anak semakin meningkat seiring perubahan pola makan dan gaya hidup. Gaya hidup yang kurang aktivitas fisik dapat mempengaruhi berat badan. Data dari Riskesdas 2010 menyatakan bahwa prevalensi obesitas pada balita di provinsi Gorontalo mencapai 7,8%. Tujuan: Diketahuinya faktor risiko aktivitas fisik terhadap obesitas pada anak di TK Al-Islah Kota Gorontalo tahun 2017. Metodologi Penelitian: Desain penelitian menggunakan case control. Sebanyak 50 anak pra sekolah dijadikan sampel penelitian. Sampel penelitian dibagi menjadi 25 anak dengan status gizi normal dan 25 anak berstatus gizi obesitas. Status gizi ditentukan berdasarkan perhitungan z-score IMT/U. Variabel aktivitas fisik ditentukan berdasarkan perhitungan dari hasil kuesioner yang diadaptasi dari penelitian Baecke. Penelitian bertempat di TK Al Islah Kota Tengah Kota Gorontalo. Penelitian dilakukan selama bulan Juli sampai dengan Agustus 2017. Hasil Penelitian: Aktivitas fisik pada siswa TK Al-Islah Kota Gorontalo, kategori aktivitas fisik baik 56,0% kategori aktivitas fisik kurang baik 44,0%. Aktivitas fisik baik dan tidak obesitas 80,0% aktivitas fisik baik dan obesitas 32,0%. Aktivitas fisik kurang baik dan tidak obesitas 20,0% dan aktivitas fisik kurang baik dan obesitas 68,0%. Ada hubungan aktivitas fisik dengan status gizi (IMT/U) siswa di TK Al-Islah tahun 2017. Kata Kunci: aktivitas fisik, obesitas, anak sekolah